Innovating in Teaching of Business Administration Through the Case Method - Chica Páez, Yolanda (Opción, 2015)
This paper describes the experience in applying the Case Method in the subject of Business Economics: Introduction. This course is taught in the first year of the Degree in Business Administration and Management, in the University of the Basque Country. In the article is detailed the context in which the implementation of the case took place and also the activities that were developed. Finally, the main results from an opinion questionnaire about this methodology given to students are presented. As a conclusion, the overall assessment of teachers is collected once the implementation of the case has finished.